2016
DOI: 10.1055/s-0036-1597275
|View full text |Cite
|
Sign up to set email alerts
|

An MRI Evaluation of Patients Who Underwent Treatment with a Cell-Mediated Gene Therapy for Degenerative Knee Arthritis: A Phase IIa Clinical Trial

Abstract: Multiple therapies have been developed to slow down the progression of knee osteoarthritis (OA), with the aim of avoiding or delaying TKA. One such potential method is cell-mediated gene therapy, which utilizes allogeneic human chondrocytes modified to express transforming growth factor-β1. Using magnetic resonance imaging (MRI), we evaluated patients who underwent treatment with this injection in a Phase II study and assessed structural changes in: (1) bone marrow edema lesions, (2) cartilage defect depth and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
2

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
0
6
0
2
Order By: Relevance
“…However, the authors concluded that these findings may be due to the natural progression of the disease rather than the injection of the transduced chondrocytes. 24…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the authors concluded that these findings may be due to the natural progression of the disease rather than the injection of the transduced chondrocytes. 24…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] Recently, a novel method for the treatment of knee osteoarthritis has been developed utilizing transduced allogeneic human chondrocytes expressing transforming growth factor-β1 (TGF-β1). [20][21][22][23][24] This cytokine regulates cell growth, differentiation, and extracellular matrix protein synthesis. In addition, it stimulates chondrocytes and has anti-inflammatory and immune suppressive effects.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Obwohl in der Praxis die konventionelle Röntgendiagnostik weiterhin der diagnostische Goldstandard ist, werden in klinischen Studien arthrotische Knorpelschäden primär per MRT quantifiziert [29]. Die MRT-Bildgebung erlaubt, das Knorpelvolumen, das mit der Gelenkspaltverschmälerung korreliert, zu messen [30].…”
Section: Bildgebende Analyse Der Longitudinalen äNderung Von Knorpeldunclassified
“…3,00 ± 0,00 [96] MRT (WORMS): stabile Befunde über 1 Jahr, als Indiz für eine Progressionsverminderung, nach 6 Monaten in Niedrigdosisgruppe Verschlechterung der Parameter "Knochenoberfläche" und "Osteophyten", in Hochdosisgruppe keine Verschlechterung, nach 1 Jahr in Niedrigdosisgruppe lediglich Parameter "Knorpelsignalintensität" und in Hochdosisgruppe Parameter "Knochenoberfläche", "Osteophyten" und "periartikuläre Entzündung" verschlechtert nein 2,33 ± 0,47 [29] Ergebnis der selektiven Literaturrecherche und Bewertung der 45 Artikel. Es wurden nur Arbeiten aufgeführt, die von mind.…”
Section: Therapie Fokaler Knorpeldefekte Als Arthroseprophylaxeunclassified